Coherent perfect absorption of single photons in a fiber network - Vetlugin, Anton N. (2019)
Large distance implementation of quantum communication technologies requires coherent control of single photons in optical fibre networks. Here we demonstrate the phenomenon of coherent perfect absorption of single photons in a fully-fiberized ultrathin plasmonic metamaterial fabricated at the end facet of an optical fibre. Continuous control of single-photon absorption probability is achieved by driving the network between the regimes of coherent total absorption and coherent total transmission. To circumvent phase fluctuations inherent to optical fibre networks, we implemented a reference-based post selection technique which yielded interference fringe visibility comparable to that of free space experiments. Coherent absorption of quantum light in fibre environment provides new opportunities for dissipative single-photon switching, filtering and measurement, as well as for manipulation of entangled, weak coherent, and NOON states in optical fibre networks.